Impact of Remittance on Household Income, Consumption and Poverty Reduction of Nepal - Bam, Nirajan; Thagurathi, Rajesh Kumar; Neupane, Deepak (Economic Literature, 2018)
The study aims to identify the impact of remittance income on household per capita income, consumption, poverty headcount ratio and poverty gap by using simple linear and log linear regression model furthermore it focused on to identify the gap of income and consumption level of upper and poor quintile population and compare the income and consumption level of different development region of Nepal by using data of Nepal living standard survey III.It was found that,remittance income has statistically significant positive impact on household per capita income and consumption.There is significant negative relationship between remittance income and proportion of poor quintile population and significant positive relationship between remittance income and richest quintile population. It indicates that due to remittance income lower quintile population was decreased significantly and richest quintile population was increased significantly. Furthermore there is inverse relationship between remittance and poverty head count ratio and poverty gap, which indicates increment on average per capita remittance income reduce the poverty headcount ratio and poverty gap. Economic Literature, Vol. XIII August 2016, page 1-8